Assessment of Workplace Automation and Employee Performance: The Synergy Between Artificial Intelligence Tools and Human Efforts in the Nigerian Educational System - Adebowale, Jegede Adepitan; Toritseju, Gedu Godwin; Perpetua, Ojike Chinyere (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2025)
This research examines the correlation between workplace automation and employee performance, focusing on the interplay between AI technologies and human contributions. The study uses a descriptive research approach and focuses on a population of workers from diverse sectors, such as banking, healthcare, and manufacturing. A sample size of 300 respondents was established via Krejcie and Morgan’s technique, and data were gathered through structured questionnaires sent via internet channels. The questionnaire included sections on demographic data, kinds of AI technologies used, and their reported effects on productivity, work satisfaction, and task efficiency. Validity and reliability were established by expert evaluations and a pilot study, with Cronbach's Alpha computed to evaluate internal consistency. The data study used statistical methods like descriptive statistics, correlation analysis, and multiple regression analysis using SPSS to assess the impact of AI tools on employee performance and the interplay between AI automation and human contributions. The findings demonstrate a substantial positive correlation between AI tools and employee performance, with AI contributing to 53.6% of the variation in performance. The data demonstrates a strong synergy between AI automation and human efforts, accounting for 62.3% of the variation in performance results.  These results highlight the need to amalgamate AI technologies with human competencies to augment productivity and cultivate a cooperative work atmosphere. The report advocates for continuous training and a learning culture to maximise the advantages of AI in the workplace, ensuring people see AI as an enhancement tool rather than a substitute.